Playful expressions of one-year-old chimpanzee infants in social and solitary play contexts - Ross, Kirsty M.; Bard, Kim A.; Matsuzawa, Tetsuro (Frontiers in Psychology, 2014)
Knowledge of the context and development of playful expressions in chimpanzees is limited because research has tended to focus on social play, on older subjects, and on the communicative signaling function of expressions. Here we explore the rate of playful facial and body expressions in solitary and social play, changes from 12- to 15-months of age, and the extent to which social partners match expressions, which may illuminate a route through which context influences expression. Naturalistic observations of seven chimpanzee infants (Pan troglodytes) were conducted at Chester Zoo, UK (n = 4), and Primate Research Institute, Japan (n = 3), and at two ages, 12 months and 15 months. No group or age differences were found in the rate of infant playful expressions. However, modalities of playful expression varied with type of play: in social play, the rate of play faces was high, whereas in solitary play, the rate of body expressions was high. Among the most frequent types of play, mild contact social play had the highest rates of play faces and multi-modal expressions (often play faces with hitting). Social partners matched both infant play faces and infant body expressions, but play faces were matched at a significantly higher rate that increased with age. Matched expression rates were highest when playing with peers despite infant expressiveness being highest when playing with older chimpanzees. Given that playful expressions emerge early in life and continue to occur in solitary contexts through the second year of life, we suggest that the play face and certain body behaviors are emotional expressions of joy, and that such expressions develop additional social functions through interactions with peers and older social partners.